The Use of Interactive Whiteboards in Teaching and Learning among Teachers of the Design and Technology Course - Mohd Yussof, Nur Arifa; Zakaria, Normah (Research and Innovation in Technical and Vocational Education and Training, 2025)
This study aims to examine the digital literacy competency in the use of Interactive Whiteboards (IWB) for Design and Technology teachers. Quantitative methods were used to conduct this study to figure out the frequency of Interactive whiteboards used among Design and Technology teachers during the Teaching and Learning session and the level of digital literacy competence in the use of IWB for Design and Technology teachers. The selection of the study sample was carried out by sampling 120 Design and Technology teachers who serve in secondary schools at Batu Pahat, Johor. The data were analyzed using the Statistical Package for the Social Sciences (SPSS) Version 27. The results of the study found that the frequency of use of IWB among Design and Technology teachers during the Teaching and Learning session was at a low level while the level of digital literacy in the use of IWB for Design and Technology teachers was also at a low level. This shows that the level of digital literacy competence in the use of IWB for Design and Technology teachers depends on the frequency of use of IWB digital technology during the Teaching and Learning session. Therefore, the school needs to be more proactive in ensuring that each classroom is equipped with interactive whiteboards as well as encouraging the use of IWB in Teaching and Learning sessions among teachers.